REINTERPRETASI HADIS PERINTAH “MEMBUNUH MANUSIA SAMPAI MENGUCAP SYAHADAT” SEBAGAI UPAYA DERADIKALISASI AGAMA - Muhammad Mundzir (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
Starting from radicalism in Indonesia in the name of Islam, this paper tries to describe how the hadith is understood about "killing human until reciting syahadat". Textual understanding of hadith cannot reflect Islam as a peaceful religion and a bearer of mercy. So, there is a need for contextual understanding and reinterpretation of the meaning of the hadith. This effort is expected to be the first step to understanding Islam as a friendly and peaceful religion. The author uses a historical and language approach to study the hadith. The result, the prophet does not order directly to fight non-Muslims but uses peaceful meaning to reflect that Islam as rahmatan lil ‘alamin. Keywords: Radicalism, Deradicalization, Jihad, Hadith about Killing Humans to recite syahadat